Uncertainty determination for activity measurements by means of the TDCR method and the CIEMAT/NIST efficiency tracing technique. (22nd May 2015) - Kossert, Karsten; Broda, Ryszard; Cassette, Philippe; Ratel, Guy; Zimmerman, Brian
Abstract: Liquid scintillation counting is a very powerful technique for the activity determination of a number of radionuclides. In radionuclide metrology, the TDCR method and the CIEMAT/NIST efficiency tracing technique are widely used in many laboratories. Both methods require rather complex calculation techniques to derive the counting efficiency of the nuclide under study. This article explores the various sources of uncertainty that should be considered when applying these two techniques, and focuses on possible ways to evaluate them. Concrete examples are provided within the paper.